The influence of risk perception, risk tolerance, overconfidence, and loss aversion towards investment decision making - Nadya Septi Nur Aini; Lutfi Lutfi (Universitas Hayam Wuruk Perbanas, 2018)
This study aims to examine the effect of risk perception, risk tolerance, overconfidence, and loss aversion on investment decision making. The sample in this study were workers in Surabaya and Jombang, East Java. There were 400 respondents taken using a questionnaire through the survey method. This study used PLS-SEM (Partial Least Square-Structural Equation Model) as a data analysis technique. The results showed that risk perception has a significant and negative effect on investment decision making, risk tolerance and overconfidence have a significant and positive effect on investment decision making, while loss aversion has no effect on investment decision making. This research is expected to provide an overview of how to deal with risk in investment and how to avoid behavioral biases in investment decisions making.